Reprogramming of DNA methylation and changes of gene expression in grafted Hevea brasiliensis - Li, Hui-Liang; Wang, Ying; Guo, Dong; Zhu, Jia-Hong; Wang, Yu; Dai, Hao-Fu; Peng, Shi-Qing (Frontiers in Plant Science, 2024)
Rubber tree (Hevea brasiliensis) is reproduced by bud grafting for commercial planting, but significant intraclonal variations exist in bud-grafted clones. DNA methylation changes related to grafting may be partly responsible for intraclonal variations. In the current study, whole-genome DNA methylation profiles of grafted rubber tree plants (GPs) and their donor plants (DPs) were evaluated by whole-genome bisulfite sequencing. Data showed that DNA methylation was downregulated and DNA methylations in CG, CHG, and CHH sequences were reprogrammed in GPs, suggesting that grafting induced the reprogramming of DNA methylation. A total of 5,939 differentially methylated genes (DMGs) were identified by comparing fractional methylation levels between GPs and DPs. Transcriptional analysis revealed that there were 9,798 differentially expressed genes (DEGs) in the DP and GP comparison. A total of 1,698 overlapping genes between DEGs and DMGs were identified. These overlapping genes were markedly enriched in the metabolic pathway and biosynthesis of secondary metabolites by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Global DNA methylation and transcriptional analyses revealed that reprogramming of DNA methylation is correlated with gene expression in grafted rubber trees. The study provides a whole-genome methylome of rubber trees and an insight into the molecular mechanisms underlying the intraclonal variations existing in the commercial planting of grafted rubber trees.